Efeito do pH, de concentrações de sais e de ágar no enraizamento in vitro de Kielmeyera coriacea (Spr.) Mart. Guttiferae - PINTO, JOSE EDUARDO BRASIL PEREIRA; ARELLO, EDUARDO FONSECA; BARBOSA, MÁRCIO HENRIQUE PEREIRA (Revista Ceres, 2015)
.